Ruin des Zusammen-lebens: Corona und die Erneuerung der Gesellschaft - Illhardt, Franz Josef (Verlag Karl Alber, 2023)
Corona showed us how important the medical and statistical data are. They inform, but are difficult to understand. We need more. We know too little about how people cope with problems, too little about what our life together depends on. We need a deeper understanding, in order to perceive the dangers to our personal and social life. This book tries to do that with thoughtfulness: it raises questions and calls apparent self-evident facts in question, it connects intellectual sources of thought by linking experiences from history, literature with the current problems of the corona crisis. And where do we go from here? Are there ways out of a battered social life to a new solidarity?